Cross-level moderating effects of teacher experience, teacher evaluation, and teacher gender on student BMI status and peer relationships among Chinese middle school students - Liu, Keyi; Miao, Chenglong (Frontiers in Psychology, 2026)
ObjectiveThis study employed Hierarchical Linear Modeling to examine the moderating roles of teacher experience, teacher evaluation, and teacher gender in the relationship between students’ BMI status and peer relationships, aiming to provide a more comprehensive understanding of how teacher-related factors shape students’ social interactions.MethodsData were drawn from the 2023–2024 academic year of the China Education Panel Survey, comprising 2,002 Chinese middle school students and their homeroom teachers from 100 schools. A two-level HLM model in which Level 1 included students’ BMI status and peer relationships, and Level 2 included teacher experience, teacher evaluation, and teacher gender as cross-level moderating variables.ResultsStudents with a normal BMI status were more likely to be accepted by their peers (β = 0.836, p < 0.001). Teacher experience had a significant positive moderating effect on the association between normal BMI status and peer relationships (β = 0.047, p < 0.001). Teacher evaluation further amplified this association (β = 0.217, p < 0.01); that is, the more experienced and the more highly evaluated the homeroom teacher, the stronger the positive impact of a normal BMI status on students’ peer relationships. Teacher gender also significantly moderated this relationship (β = 0.246, p < 0.05), with the beneficial effect of a normal BMI status on peer relationships being more pronounced in classes taught by female teachers.ConclusionNormal BMI status has a significant positive effect on peer relationships, and this association is cross-level moderated by teacher experience, teacher evaluation, and teacher gender. Higher teacher experience, higher teacher evaluation, and classrooms led by female teachers strengthen the positive effect of normal BMI status. These findings highlight the critical role of teacher-related factors in shaping students’ social ecology and provide empirical support for optimizing educational environments and promoting social equity among students.